Assessment of the quality of life in type 2 diabetes patients – a comparative study of WHOQOL-BREF and DQOL instruments - Asti, Arnika Dwi; Sarwono; Kinwati; Suwaryo, Putra Agina Widyaswara (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Type 2 diabetes mellitus (T2DM) is a prevalent health issue that significantly impacts the quality of life of patients. Evaluating quality of life in T2DM patients is crucial for understanding the broader effects of the disease and improving patient care. This study aims to evaluate and compare the effectiveness of the WHOQOL-BREF and DQOL instruments in measuring the quality of life of T2DM patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A descriptive quantitative study was conducted from March to June 2023 at Puskesmas Wanadadi 1 Banjarnegara. The sample consisted of 195 T2DM patients selected using purposive sampling based on the following inclusion criteria: diagnosed with T2DM for at least one year, aged 30-70 years, willing to participate, and able to complete the questionnaires. Data were collected using the WHOQOL-BREF and DQOL questionnaires and analyzed descriptively. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The analysis revealed that the WHOQOL-BREF and DQOL instruments provided comprehensive insights into the quality of life of T2DM patients. The WHOQOL-BREF was particularly effective in assessing physical and environmental domains (p<0.05), while the DQOL was more sensitive to diabetes-specific concerns and psychological well-being (p<0.05). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Both the WHOQOL-BREF and DQOL are effective in evaluating the quality of life of T2DM patients, each offering unique strengths in different domains. The findings suggest that a combined use of these instruments could provide a more holistic understanding of the quality of life impacts in T2DM patients, guiding more targeted interventions to improve patient outcomes.